Hate crime and reverse engineering the law - Carlson, Kerstin Bree (Courtroom ethnography, 2023)
This chapter explores how ethnographic observation of the trial and appeal reveals the applied judicial logic regarding how to assess criminal hate. Focusing on one racialized murder on the Danish island of Bornholm, the chapter shows how ethnography illuminates an interesting contrast between judicial constructions of intent and motivation. Both are legal fictions, designed to connect facts as committed to laws and the ideologies they represent. Ethnography reveals how the parties (prosecutor, defense, judges) in the Bornholm first-instance and appeals trials engaged in creative, active judicial constructions as regards intent, but narrow, static constructions regarding motivation. This is interesting, since motivation is arguably the more readily demonstrable psychological impetus. Ethnography demonstrates how in the Bornholm murder case, the parties used ‘intent’ to investigate and ‘motivation’ to declare.